Elementary aspects of the political : histories from the Global South - Banerjee, Prathama (Durham : Duke University Press, 2020)
"In Elementary Aspects of the Political Prathama Banerjee moves beyond postcolonial and decolonial critiques of European political philosophy to rethink modern conceptions of "the political" from the perspective of the Global South. Drawing on Indian and Bengali practices and philosophies from the late nineteenth and early twentieth centuries, Banerjee identifies four elements of the political: the self, action, ideas, and the people. She examines selfhood in light of precolonial Indic traditions of renunciation and realpolitik; action in the constitutive tension between traditional conceptions of karma and modern ideas of labor; the idea of equality as it emerges in the dialectic between spirituality and economics; and people in the friction between the structure of the political party and the atmospherics of fiction and theater. Throughout, Banerjee reasserts the historical specificity of political thought and challenges modern assumptions about the universality, primacy, and self-evidence of the political. In formulating a new theory of the political, Banerjee gestures toward a globally salient political philosophy that displaces prevailing Western notions of the political masquerading as universal"--
The Self -- Renunciation and Antisocial Being -- Philosophy, Theater, and Realpolitik -- Action -- Karma, Freedom, and Everyday Life -- Labor, Hunger, and Struggle -- Idea -- Equality and Spirituality -- Equality and Economic Reason -- People -- People as Party -- People as Fiction.
Includes bibliographical references and index.
Keywords: Political science -- India; Political science -- Philosophy